2010
DOI: 10.3141/2178-19
|View full text |Cite
|
Sign up to set email alerts
|

To What Extent Can High-Occupancy Vehicle Lanes Reduce Vehicle Trips and Congestion?

Abstract: Despite the increasing interest in and deployment of managed lanes on highways that involve pricing and tolling schemes, a considerable number of highway facilities still use high-occupancy vehicle (HOV) lanes with no other features to manage or price their use. These HOV lanes are often restricted to vehicles transporting two or more, or three or more, occupants and are viewed as mechanisms to reduce vehicular travel demand, motivate ridesharing among individuals, and curb greenhouse gas emissions. In this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Bard (1997) looks at how carpooling decreases the total number of trips taken by a household, but does not extend this to traffic outcomes or welfare calculations. Plotz, Konduri, and Pendyala (2010) put bounds on how many carpools were formed because of HOV lanes. Lee (1984) looks at the optimal number of people in a carpool and Ferguson (1997) studies trends in carpooling.…”
Section: Additional Models Of Hov and Hot Lanesmentioning
confidence: 99%
“…Bard (1997) looks at how carpooling decreases the total number of trips taken by a household, but does not extend this to traffic outcomes or welfare calculations. Plotz, Konduri, and Pendyala (2010) put bounds on how many carpools were formed because of HOV lanes. Lee (1984) looks at the optimal number of people in a carpool and Ferguson (1997) studies trends in carpooling.…”
Section: Additional Models Of Hov and Hot Lanesmentioning
confidence: 99%
“…The technique of (HOV) lanes is a disputable way to eliminate traffic congestions [2,3], for the reason that HOV will succeed to eliminate congestions, only if traffic congestions refuse to go away. I. e. there is a need for ongoing congestions in the general purpose lanes so as to convince the drivers to shift to the HOV lane, otherwise the HOV lanes will have no effect [4].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Dahlgren (1998) pointed out that in certain condition, adding a HOV lane to a three-lane freeway can be less effective than adding a general-purpose lane. Plotz et al (2010) concluded that pure HOV lanes contribute little to relieving congestion without additional managed use and pricing features. Almost all previous studies have been conducted on specific scenarios, which contribute to the substantial divergence in the findings.…”
Section: Literature Reviewmentioning
confidence: 99%